Adapting mentoring to individual differences in novice teacher learning: the mentor's viewpoint. Issue 2 (17th February 2016) - van Ginkel, Gisbert; Oolbekkink, Helma; Meijer, Paulien C.; Verloop, Nico
Abstract : Being adaptive to the individual novice teacher is considered a condition for effective teacher mentoring. The aims of this study are therefore to explore (1) mentoring activities through which mentors intend to adapt to the individual novice teacher and (2) characteristics of adaptive mentors. Information was collected through on-site, post-mentoring conversation interviews with 18 mentors holding different mentoring conceptions, from different programs for Initial Teacher Education in the Netherlands. Four adaptive mentoring activities were identified: (1) aligning mutual expectations about the mentoring process, (2) attuning to the novices' emotional state, (3) adapting the mentoring conversation to match the reflective capacity of the novice teacher, and (4) building tasks from simple to complex relative to the novices' competence level. Adaptive mentors were (1) more likely to mention activities intended to support construction of personal practical knowledge and (2) less likely to mention activities intended to create a favourable context for novice teacher learning. Suggestions for using findings to enhance mentor adaptiveness are discussed.